A master plan for the city: looking at the past - Dossal, Mariam (2005)
A play of vested interests has always ensured the shelving of successive master plans devised for the city's planned development. This article looks at efforts to `improve' Mumbai, initiated in the last 1890s and the early years of the last century, following the outbreak of the plague epidemic. The story of how such initiatives were stymied by groups comprising traders and developers acting in concert, is in turn revelatory of how little seems to have changed over the decades. - Reproduced.
Keywords: Urban planning